Mechanisms by which autophagy regulates memory capacity in ageing. Issue 9 (30th July 2020) - De Risi, Maria; Torromino, Giulia; Tufano, Michele; Moriceau, Stéphanie; Pignataro, Annabella; Rivagorda, Manon; Carrano, Nicolò; Middei, Silvia; Settembre, Carmine; Ammassari‐Teule, Martine; Gardoni, Fabrizio; Mele, Andrea; et al.
Abstract: Autophagy agonists have been proposed to slow down neurodegeneration. Spermidine, a polyamine that acts as an autophagy agonist, is currently under clinical trial for the treatment of age‐related memory decline. How Spermidine and other autophagy agonists regulate memory and synaptic plasticity is under investigation. We set up a novel mouse model of mild cognitive impairment (MCI), in which middle‐aged (12‐month‐old) mice exhibit impaired memory capacity, lysosomes engulfed with amyloid fibrils (β‐amyloid and α‐synuclein) and impaired task‐induced GluA1 hippocampal post‐translation modifications. Subchronic treatment with Spermidine as well as the autophagy agonist TAT‐Beclin 1 rescued memory capacity and GluA1 post‐translational modifications by favouring the autophagy/lysosomal‐mediated degradation of amyloid fibrils. These findings provide new mechanistic evidence on the therapeutic relevance of autophagy enhancers which, by improving the degradation of misfolded proteins, slow down age‐related memory decline. Abstract : We developed a novel mouse model of mild cognitive impairment (MCI) that allows to identify middle‐aged (12‐month‐old) mice with impaired memory capacity and vulnerable to age‐dependent memory decline. Spermidine and TAT‐Beclin 1, by stimulating autophagy/lysosomal degradation of misfolded protein, reduce the amyloid load and rescue the memory‐dependent post‐translational modifications of GluA1 receptors in the hippocampus of the cognitively impaired ageing mice.